Primary school students’ implicit theories and their reading motivation. The role of parents’ and teachers’ effort feedback - Hellmich, Frank; Hoya, Fabian Karl (Zeitschrift für Psychologie)
Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The results of a structural equation model show that children’s perceptions of their parents’ effort feedback predict their implicit theories, their reading self-concepts, and their reading motivation. The correlation between children’s perceived parental effort feedback and their intrinsic reading motivation is mediated by their implicit theories. Children’s implicit theories and their reading motivation cannot be predicted by their perceptions of their teachers’ effort feedback.